Persepsi Orang Tua Dalam Penggunaan Gadget Pada Anak Sd Di Perkotaan Dan Pinggiran Di Kota Blora - Trixie Salawati (Universitas Pekalongan, 2021)
The use of gadgets among children is now starting to increase. According to digital research data, the use of gadgets in Indonesia has increased every year, namely in 2016 as many as 65.2 million, until in 2019 as many as 97 million. Based on observations in Blora, it is known that there are some children who use gadgets without parental supervision and are not given a time limit. So this research was conducted to determine the perceptions of parents in the use of gadgets in elementary school children in urban and suburban areas in Blora City. Comparative research using cross sectional approach. Samples were taken as many as 100 people in urban elementary schools and 100 people in suburban primary schools. Data analysis used normality test using Kolmogorof Smirnov 1 sample test and Independent t-test. From the research results, it is known that the majority of respondents in urban areas have a 100% positive perception. However, only 67% of respondents in the suburbs had a positive perception. The results of the statistical test on the perceptions of parents in the use of gadgets in urban elementary school children with the parents' perceptions of using gadgets in rural elementary school children, it is known that the value of p = 0.000 (p